2014
DOI: 10.1037/a0032817
|View full text |Cite
|
Sign up to set email alerts
|

The role of attention in motor control.

Abstract: Research on the focus of attention (FOA) in motor control has found a consistent advantage for focusing externally (on the effects of one's actions) compared to focusing internally (on one's body mechanics). However, most of this work has concentrated on movement outcomes, leaving open the question of how external attention changes the movement itself. Somewhat paradoxically, recent research has found that external attention also increases trial-by-trial movement variability. To explain these findings, we prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
70
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 73 publications
7
70
1
Order By: Relevance
“…Given the outlined descriptions of movement coordination and synergies, PCA can provide interpretations in line with concepts from motor control (Latash, 2010;Li, 2006;Lohse et al, 2013;Scholz & Schoner, 1999), providing a multivariate time series measure of movement variability. Collectively, PCA has been applied to datasets from kinematic, kinetic, and EMG sources, demonstrating utility among a number of tasks (Daffertshofer et al, 2004;Kipp, Redden, Sabick, & Harris, 2012;Kipp et al, 2014;Li, 2006;Richter et al, 2014).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Given the outlined descriptions of movement coordination and synergies, PCA can provide interpretations in line with concepts from motor control (Latash, 2010;Li, 2006;Lohse et al, 2013;Scholz & Schoner, 1999), providing a multivariate time series measure of movement variability. Collectively, PCA has been applied to datasets from kinematic, kinetic, and EMG sources, demonstrating utility among a number of tasks (Daffertshofer et al, 2004;Kipp, Redden, Sabick, & Harris, 2012;Kipp et al, 2014;Li, 2006;Richter et al, 2014).…”
Section: Introductionmentioning
confidence: 95%
“…During movement execution, the available biomechanical degrees of freedom (DOF) exceed those required to successfully perform a task (Bernstein, 1967;Davids, Glazier, Araujo, & Bartlett, 2003). Movement coordination is therefore simplified through dimension reduction (Latash, 2010;Lohse, Jones, Healy, & Sherwood, 2013;Turvey, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in skilled dart players it was observed that smaller release angles were compensated by higher velocities of the dart, and vice versa (Loosch, 1995;Wulf & Prinz, 2001). Lohse and colleagues (Lohse, Jones, Healy, & Sherwood, 2014;Lohse, Sherwood, & Healy, 2010) demonstrated that an external focus also leads to greater functional variability than an internal focus.…”
Section: External Focus Promotes Automaticitymentioning
confidence: 99%
“…Indeed, a recent study by Russell, Porter, and Campbell (2014) showed nicely that an external focus on the primary task (dart throwing) was necessary to enhance performance, whereas an external focus on a simultaneously performed secondary task-which should have directed attention away from the self-was not able to enhance performance (similar to internal foci on either task). The consequence of focusing on the intended effect is a coordination pattern that resembles one that is typically seen at a more advanced skill level-with a more efficient recruitment of motor units, fewer co-contraction of agonists and antagonists (Lohse & Sherwood, 2012), greater force output (Marchant, Greig, & Scott, 2009), a "freeing" of the body's degrees of freedom (Wulf & Dufek, 2009;Wulf, 2013), increased functional variability (Lohse et al, 2014;Wulf & Prinz, 2001), and generally increased movement accuracy. How exactly the motor system accomplishes this is perhaps one of most intriguing questions.…”
Section: Mechanisms For Attentional Focus Effectsmentioning
confidence: 99%
“…An external focus facilitates automaticity as evidenced by reduced attentional demands (Kal, van der Kamp, & Houdijk, 2013;Wulf, McNevin, & Shea, 2001), high-frequency movement corrections indicating greater involvement of reflexes (e.g., McNevin, Shea, & Wulf, 2003), increased functional variability (Lohse, Jones, Healy, & Sherwood, 2013), and greater movement fluidity (Kal et al, 2013). As a result, an external focus speeds the learning process relative to an internal focus which tends to interfere with automatic processes (Wulf et al, 2001).…”
Section: Introductionmentioning
confidence: 99%